The Air That We Breathe: Addressing the Risks of Global Urbanization on Health - The PLOS Medicine Editors (PLOS Medicine, 2012)
The PLOS Medicine Editors discuss the need for transparent urban air quality indicators across the global and especially in low- and middle-income countries.